2005
DOI: 10.1103/physrevlett.95.035302
|View full text |Cite
|
Sign up to set email alerts
|

Emission of Discrete Vortex Rings by a Vibrating Grid In SuperfluidHe3B: A Precursor to Quantum Turbulence

Abstract: We report a transition in the vorticity generated by a grid moving in the B phase of superfluid 3He at T< Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(36 citation statements)
references
References 12 publications
1
35
0
Order By: Relevance
“…4, where wire 4 detects a fast vortex ring signal at the same time as the nearer wires detect turbulence. Coexistence of quantum turbulence and primary vortex rings was observed in measurements with the earlier grid, but only very close to the transition region (54).…”
Section: Decay Of the Vortex Signalmentioning
confidence: 93%
See 1 more Smart Citation
“…4, where wire 4 detects a fast vortex ring signal at the same time as the nearer wires detect turbulence. Coexistence of quantum turbulence and primary vortex rings was observed in measurements with the earlier grid, but only very close to the transition region (54).…”
Section: Decay Of the Vortex Signalmentioning
confidence: 93%
“…These have a greater chance of further recombinations resulting in the production of a vortex tangle (quantum turbulence). The above scenario was first inferred from measurements of the decay of the vortex signal (54) and was confirmed by numerical simulations (56). We can obtain more detailed information from the steady-state regime by studying fluctuations, as discussed below.…”
Section: Spatial Correlations Of Vortex Ringsmentioning
confidence: 99%
“…Here it is worth mentioning that the investigation of evolving vortex string networks has a tradition in different areas of physics from topological defects in solids to cosmic strings (Vilenkin and Shellard, 1994). Many aspects of the associated dynamical rules and the generation of entangled string networks have also been extensively studied for superfluid turbulence [for surveys see Schwarz (1982); Martins et al (2004);Bradley et al (2005)]. The predicted richness of possible behaviors has not yet been fully identified in cyclically dominated three-state games.…”
Section: Rotating Spiral Armsmentioning
confidence: 99%
“…The important role that vortex rings occupy in the study of quantum turbulence has prompted detailed experimental studies of these excitations in both 4 He and 3 He 2,17 . This has revealed that the number density of vortex rings strongly determines the likelihood of neighbouring vortex rings to reconnect.…”
Section: Introductionmentioning
confidence: 99%